Raccontare l’altro. Primo Levi, il personaggio non finzionale, l’etopea (ENTHYMEMA, 2020)
Se questo è un uomo displays a classification of Lager’s victims. By combining scientific methods with literary tools, Primo Levi resumes the ancient tradition of the ethopoeia. Accordingly, he tackles the specific issues stemming from the portrayal of nonfictional characters. They are built up according to the need to form a moral judgement and therefore the concepts the writer employs to define them must be more explicit and unambiguous than those employed in fictional writing.